Biostratigraphy, paleoenvironment and paleoclimate in northeastern Patagonia during the early Paleocene based on the micropaleontological record - González Estebenet, M. Sol (2025)
The Península Vald´es es-1 well exhibits the most complete stratigraphic record of an important Danian Atlantic marine event in Patagonia, Argentina. Biostratigraphic analysis of organic-walled dinoflagellate cysts (dinocysts) along with sporomorphs, calcareous nannofossils and foraminiferal complementary data allowed the identification of three stratigraphic intervals of earliest Danian, early to middle Danian and late Danian ages. Diagnostic palynomorph events were recognized including the highest occurrences of the dinocysts Danea californica and Senoniasphaera inornata; the highest common occurrences of Trithyrodinium evittii and Trithyridinium verrucosum. A basal spike of the Cheirolepidiaceae pollen Classopollis provides further evidence of the flourishing of this opportunistic taxon in disturbed ecosystems related to the K/P mass extinction event. The nannofossil zones NP1 to NP4 were identified throughout the section, as well as the foraminifera zones P1b–P1c in the middle and upper part. The microfossil composition reveals fluctuating proximal and neritic environments, as well as a maximum flooding episode; the latter, indicated by the outer neritic Spiniferites, the oceanic taxa Impagidiniumr, along with a glauconitic level. Two warm-sea surface temperature episodes were identified; the oldest, in the early Danian, indicated by the thermophilic dinocysts Trithyrodinium, Hafniasphera and Cordospheridium; and the youngest, in the late Danian, marked by Glaphyrocysta, Hafniasphaera, Tectatodinium pellitum and Pierceites spp. together with frost-intolerant sporomorph taxa and the warm-water foraminifer Boltovskoyella paleocenica. This study contributes to the Argentina paleogeography, achieving a refined marine reconstruction model for the early Paleocene.